Issues and Trends in Brazilian Studies in South Korea: Social Sciences and Humanities - Jung, Hoyoon (Brasiliana: Journal for Brazilian Studies, 2021)
As Brazil emerges as a significant and influential country in the global arena, studies related to Brazil have drawn keen scholarly interests from a number of fields of study. In this regard, “Brazilian Studies” has grown considerably in the last several decades and has solid representation in most disciplines, particularly in the social sciences and humanities. In South Korea, Brazilian Studies has also become a competitive and promising discipline through the effort of pioneer Korean brazilianists, yet less lively compared to Brazilian Studies in the United States and other European countries that have guided this field. Employing web-based methods, including online-based searching, and bibliographical analysis based on the data collected by DBpia, this study aims to introduce and examine the issues, trends and current state of Brazilian Studies education and research in South Korea, particularly focusing on the social sciences and humanities.